2021
DOI: 10.1016/j.cattod.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

UV-A light-assisted gas-phase formic acid decomposition on photo-thermo Ru/TiO2 catalyst

Abstract: Although solar energy is considered as one of the ideal abundant sources of renewable energy to be integrated into catalytic processing, photonic and thermal excitations were perceived till recently as independent strategies in overcoming Arrhenius-type activation energy barriers in catalytic reactions. However, this dual-mode excitation of catalysts is receiving a growing interest nowadays due to promising evidence of synergy effects. A Ru/TiO2 photo-thermo-catalyst was prepared according to a UV-A light phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 59 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…[13][14][15][16] The co-catalysts include oxides, sulfides, carbides, and metals. Furthermore, metallic nanoparticles, such as Ag, 17 Au, 18 Pt, 19 Pd, 20 and Ru, 21 have been widely used in photocatalysis employing TiO 2 and other semiconductors. Numerous studies have shown that the photoinduced electrons in TiO 2 can transfer to metallic nanoparticles in a very short time, and thus the charge carriers are effectively separated.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The co-catalysts include oxides, sulfides, carbides, and metals. Furthermore, metallic nanoparticles, such as Ag, 17 Au, 18 Pt, 19 Pd, 20 and Ru, 21 have been widely used in photocatalysis employing TiO 2 and other semiconductors. Numerous studies have shown that the photoinduced electrons in TiO 2 can transfer to metallic nanoparticles in a very short time, and thus the charge carriers are effectively separated.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium oxide is regarded as the first semiconductor for photocatalyst-based water splitting [ 16 ], but because of a large band gap (3.2 eV) [ 110 ], it can only utilize UV radiation [ 111 ], which accounts for only a small portion of the solar spectrum. Still, many studies improved upon TiO 2 photocatalysts.…”
Section: Modern Developments In Photocatalysts For High-kinetic Water...mentioning
confidence: 99%
“…43 A similar reaction mechanism but from formic acid as the initial reactant instead of an alcohol has been shown to occur with Ru/TiO 2 . 71 As for the methanol case, the formate type species, decarbonylation type reactions leading to CO as well as the generation of carbon dioxide were promoted under thermo-photo conditions.…”
Section: Interpretation Of Excess Functionsmentioning
confidence: 99%